The future of surplus dairy calves – an animal welfare perspective - Webb, Laura E.; Verwer, Cynthia; Bokkers, Eddie A. M. (Frontiers in Animal Science, 2023)
An important obstacle toward sustainably produced animal-source food is the existence of so-called ‘surplus animals’, which are by-products of the production of dairy products and eggs, and ‘unwanted’ due to their perceived low value. Although this depends on the country, in Europe many surplus dairy calves are transported to veal farms to be raised for 6 months until slaughter. The aim of this article is to present ideas for alternative future systems for the dairy-veal chain, including an overview of current challenges and improvement strategies for calf welfare. This dairy-veal chain presents a number of potential concerns for calf welfare, including transportation of young animals, high risk of disease and barren housing. Many incremental changes have been suggested in past literature to lift the welfare of veal calves, including reducing transportation, transporting calves at an older age, better health screening, and pens with enrichment and bedding. The Netherlands is at the centre of the veal sector import-export flow in Europe and is one of the main veal producers in the world. The Dutch government has recently presented a report with three alternative ‘scenarios’ for the raising of these surplus dairy calves, which are expected to lead to improvements in animals welfare. The first scenario is a restriction on transport of <100km, leading to more local production of dairy-veal. The second scenario is a delay on the transportation of surplus calves from 2 weeks to 3 months of age, handing dairy farmers a much larger role in the raising of these calves. This delay would ensure that calves are more robust and less vulnerable to disease at the time that they are transported to the veal farm. The third scenario proposes an alternative system, where the veal sector is eradicated and surplus dairy calves are raised at the dairy farm of origin until slaughter. We, like others before us, question the impact of small incremental changes on calf welfare, arguing that improvements at one end could potentially lead to worsening of welfare at the other end, and prefer to focus on system changes, such as the use of dual-purpose cattle breeds. We do not however believe that system changes can be created and implemented with the sole input of animal welfare scientists. This work is hence just one piece of the puzzle towards the sustainable production of milk and meat, and more specifically the sustainable rearing of surplus calves.